The Activity Theory Approach to Learning - Ritva Engeström (University of Lower Silesia, 2014)
In this paper the author offers a practical view of the theory-grounded research on education action. She draws on studies carried out at the Center for Research on Activity, Development and Learning (CRADLE) at the University of Helsinki in Finland. In its work, the Center draws on cultural-historical activity theory (CHAT) and is well-known for the theory of Expansive Learning and its more practical application called Developmental Work Research (DWR). These approaches are widely used to understand professional learning and have served as a theoreticaland methodological foundation for studies examining change and professional development in various human activities.